Understanding Bhutanese Refugee Suicide Through the Interpersonal-Psychological Theory of Suicidal Behavior - Ellis, B. Heidi (Am J Orthopsychiatry, 2015)
Attention has been drawn to high rates of suicide among refugees after resettlement and in particular among the Bhutanese refugees. This study sought to understand the apparent high rates of suicide among resettled Bhutanese refugees in the context of the Interpersonal-Psychological Theory of Suicidal Behavior (IPTS). Expanding on a larger investigation of suicide in a randomly selected sample of Bhutanese men and women resettled in Arizona, Georgia, New York, and Texas (Ao et al., 2012), the current study focused on 2 factors, thwarted belongingness and perceived burdensomeness, examined individual and postmigration variables associated with these factors, and explored how they differed by gender. Overall, factors such as poor health were associated with perceived burdensomeness and thwarted belongingness. For men, stressors related to employment and providing for their families were related to feeling burdensome and/or alienated from family and friends, whereas for women, stressors such as illiteracy, family conflict, and being separated from family members were more associated. IPTS holds promise in understanding suicide in the resettled Bhutanese community.